ON THE NATIONAL MARKING OF SOMATIC UTTERANCES - Dildarkhan Urinbaevna Hashimova (American Journals Publishing, 2023)
It is known that somatic utterances in any language reflect aspects of culture and everyday life and are unique facts of the original historical development of a particular people. This article analyzes the lacunae - somatic utterances that exist in the modern Russian literary language.
Keywords: somatism, culture, meaning, component, vocabulary, variation, history, identity, speech, fact, tracing paper; somatic speech, somatic phraseology, non-equivalent vocabulary, cultural component, literary work, additional meaning, non-verbal behavior, representative of another linguistic community, original historical development of the people.